Pendidikan Kemuhammadiyahan (AIK) Sebagai Ruh PergerakanPendidikan Di STIT Internasional Muhammadiyah Batam - Suyono (Hamka Ilmu Pendidikan Islam, 2023)
Muhammadiyah has a distinctive characteristic in its educational movement which it has managedsincethisorganization was founded by Kiai Ahmad Dahlan in 1912. The thoughts and actions as well as the philosophyofeducation pursued by Kiai Ahmad Dahlan have become the subject of research discussion by domesticandforeign researchers. Incorporating the Islamic religious curriculum into public schools and incorporatinggeneralscience teaching into Islamic-based education was a breakthrough by Kiai Ahmad Dahlan at that time. Nowtheteaching of Al-Islam Kemuhammadiyahan both in tertiary institutions and Muhammadiyah schools has becomeits own characteristic which is able to maintain the spirit of the educational movement and the Muhammadiyahmovement in general. The teaching of Al-Islam KeMuhammadiyahan continues to receive major attentioninorder to maintain the spirit of the Muhammadiyah movement. Keywords: Kemuhammadiyahan, Education Motivator